Methotrexate related adverse effects in patients with rheumatoid arthritis are associated with the A1298C polymorphism of the MTHFR gene. Issue 10 (10th September 2004) - Berkun, Y; Levartovsky, D; Rubinow, A; Orbach, H; Aamar, S; Grenader, T; Abou Atta, I; Mevorach, D; Friedman, G; Ben-Yehuda, A
Abstract : Background: There is an association between C677T polymorphism of the methylenetetrahydrofolate reductase (MTHFR) gene and methotrexate related toxicity. Objective: To examine the relations between the recently described A1298C polymorphism of the MTHFR gene, plasma homocysteine, methotrexate toxicity, and disease activity in patients with rheumatoid arthritis. Design: A cross sectional study on 93 methotrexate treated patients with rheumatoid arthritis, comprising a clinical interview and physical examination to determine disease activity and methotrexate related adverse reactions. Genotype analysis of the MTHFR gene was carried out and fasting plasma homocysteine and serum folate concentrations were measured. The data were analysed using univariate analysis. Allele and genotype distributions were compared with those of a healthy control group. Results: The frequency of the 1298CC genotype (24.7%) in the rheumatoid study group was greater than expected in the general population (12.8%, p<0.001). This genotype was associated with a significantly low rate of methotrexate related side effects. The odds ratio for side effects in patients with wild type 1298AA genotype v 1298CC genotype was 5.24 (95% confidence interval, 1.38 to 20). No correlation of disease activity variables or plasma homocysteine with MTHFR A1298C and C677T polymorphisms was observed. Conclusions: 1298CC polymorphism was more common in methotrexate treated rheumatoid patients than expected in the population, and was associated with a reduction in methotrexate related adverse effects. The A1298C polymorphism of the MTHFR gene may indicate a need to adjust the dose of methotrexate given to patients with rheumatoid arthritis.